New zinc and cadndum chalcogenide structured nanoparticles - Daniels, S; O'Brien, P; Pickett, N; Smith, J (2004)
The growth of 2D quantum dot quantum well (QDQW) nanocrystals in which a shell of CdSe is grown onto cores of ZnS and capped with a further shell of ZnS is reported. The red shift in the interband absorption and photoluminescence spectrum of the quantum dots (QDs) indicates relocalization of carriers from confinement in the ZnS core to the CdSe shell. The change in interband absorption energy utilizing the effective mass approximation with spherical symmetry was modeled, enabling an estimate of the CdSe thicknesses grown. 1.8 mn and 2.5 nm ZnS cores were selected as the base on which to grow the CdSe shells. Despite the 12% lattice mismatch between ZnS and CdSe, our results indicate that we have successfully grown CdSe shells approximately three monolayers thick onto 2.5 nm ZnS core. Anything beyond a single monolayer of CdSe could not be grown onto the 1.8 nm core, although some success was observed by incorporating a CdS graded layer in-between the ZnS core and CdSe shell. The effect of ZnS shell thickness on photoluminescence efficiency has also been studied with optimum shell thicknesses showing quantum yields as high as 52%. Growth of these nanocrystals represents a significant step in the development of strained nanocrystalline heterostructures.